Anti-diabetic and anti-inflammatory activities of Marrubiin isolated from Marrubium vulgare: Indications of its interaction with PPAR γ - Parveen Kumar; Shabir A. Dar; Omesh Manhas; Anil Bhushan; Prasoon Gupta; Sreedhar Madishetti; Zabeer Ahmed (Elsevier, 2024)
Background: The aerial parts of Marrubium vulgare L. were used for many ailments like catarrh to diabetes in many parts of Latin America and Asia. Purpose: Identifying the active principle responsible for anti-diabetic activity of methanol extract of M. vulgare leaves and to predict the possible targets. Study design: All the activity investigations were conducted simultaneously for the extract, fraction, and isolated compounds to decipher the activity profile in comparison to each other which allowed the identification of an active principle followed by use of in silico methods to identify the possible target/s. Methods: The aerial parts of M. vulgare were extracted using methanol. A chloroform fraction was prepared. Marrubiin and marrubinone B were isolated from this fraction. The anti-hyperglycemic, hypoglycemic, and postprandial blood glucose lowering activities were investigated using streptozotocin-induced diabetic and non-diabetic rat models. Pro-inflammatory cytokine inhibitory potential was investigated using LPS induced acute-inflammatory mouse model and RAW 264.7 cells. Further, antioxidant activity was investigated using a DPPH assay. The in silico analysis, using the Swiss-target prediction tool, was carried out to predict the probable targets of the isolated molecules. Results: Marrubiin exhibited anti-hyperglycemic effect in diabetic rats followed by hypoglycemia, and postprandial blood glucose lowering in non-diabetic rats. Methanol extract (Mv extract) and chloroform fraction (Mv fraction) showed anti-hyperglycemic and hypoglycemic effects. Moderate inhibition of IL-1β, TNF-α, and IL-6 was observed for marrubiin, marrubinone B, Mv extract, and Mv fraction, in vitro and in vivo. Neither marrubiin nor marrubinone B could quench the DPPH free radicals while Mv extract and Mv fraction could show 80 % suppression. In silico analysis has predicted that marrubiin can interact with PPAR γ but not marrubinone B. Conclusions: Marrubiin and marrubinone B were responsible for the anti-inflammatory effect of Mv extract and Mv fraction while not contributing to the antioxidant effect. Marrubiin was found to be responsible for the anti-diabetic activity of Mv extract. The predicted interaction propensity of marrubiin with PPAR γ could explain its dual activity observed in the experimental setup.